Retention mechanisms of microplastics in soil environments during saturation-desaturation cycles: Impact of hydrophobicity and pore geometry - Ahmed Elrahmani (17128837) (2025)
Forming ubiquitous contaminants in sediments, microplastics (MPs) are of growing concern due to their rapid infiltration into the environment and detrimental effects on ecosystems and human health. Understanding MP transport dynamics in pore networks is essential for predicting their mobility in sediments and soils and developing strategies to mitigate their spread. This study examines how pore geometry and MP hydrophobicity affect retention mechanisms within porous media during saturation-desaturation cycles. Microfluidic experiments were conducted using micromodels representing porous media with varied pore characteristics. MPs with hydrophilic, hydrophobic, and mixed hydrophobicity properties were introduced into these micromodels, and high-resolution imaging analyzed their retention patterns. The results reveal distinct retention behaviors based on MP hydrophobicity and pore geometry. Hydrophilic MPs were retained through clustering and sieving within smaller throats, particularly in low-connectivity geometries, with retention reaching 25 %. Hydrophobic MPs attached strongly to the solid-water interface (SWI) during saturation and shifted to the air-water interface (AWI) during desaturation, achieving retention rates up to 40 % in high-connectivity geometries. Mixed MPs exhibited combined behaviors, with early SWI attachment and subsequent clustering and sieving, resulting in retention rates as high as 50 % in geometries with high specific surface areas. These findings highlight the role of pore geometry and MP surface properties in determining retention and mobility. Hydrophilic MPs form contamination hotspots in fine-grained sediments, while hydrophobic MPs are more mobile in high-connectivity environments. Mixed MPs persist due to multiple retention mechanisms, posing challenges for remediation. This study informs strategies to manage MP contamination in subsurface environments. Other Information Published in: Science of The Total Environment License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.scitotenv.2025.179238